2019
DOI: 10.1002/jbt.22410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crocin in reducing DNA damage, inflammation, and oxidative stress in multiple sclerosis patients: A double‐blind, randomized, and placebo‐controlled trial

Abstract: Multiple sclerosis (MS) is an autoimmune disease in which the immune system attacks the nerve cells, resulting in neurological disorders. Oxidative stress, free radicals, and neuritis have important roles in MS pathogenesis. Here, we aim to evaluate the effect of crocin on inflammatory markers, oxidative damage, and deoxyribonucleic acid (DNA) damage in the blood of patients with MS. A total of 40 patients were divided into two groups, drug and placebo‐treated groups, using random assignment. Participants of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 27 publications
2
47
0
Order By: Relevance
“…TAC increased in the saffron group and decreased in the control group at the end of the current study, also there was a significant difference in TAC change between the supplement and placebo groups. Similar to our results, Ghiasian et al found a significant increase in serum level of TAC in the Crocin group (30 mg) compared to the control group in MS patients (Ghiasian et al, 2019). An animal study reported that 0.063, 0.25, and 1 mg/kg Safranal significantly increased TAC activity and dose‐dependently reduced wound area (Tamaddonfard et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…TAC increased in the saffron group and decreased in the control group at the end of the current study, also there was a significant difference in TAC change between the supplement and placebo groups. Similar to our results, Ghiasian et al found a significant increase in serum level of TAC in the Crocin group (30 mg) compared to the control group in MS patients (Ghiasian et al, 2019). An animal study reported that 0.063, 0.25, and 1 mg/kg Safranal significantly increased TAC activity and dose‐dependently reduced wound area (Tamaddonfard et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The duration of intervention ranged between 4 and 12 weeks. Seven studies were conducted on both genders (Azimi et al, 2016; Ebrahimi et al, 2019; Ghaderi et al, 2019; Ghiasian et al, 2019; Kermani et al, 2017; Mohamadpour et al, 2013; Shahbazian et al, 2019) while only one study was performed exclusively on males (Mousavi et al, 2015). The total sample size of the included RCTs was 472 individuals (248 subjects in the saffron group and 224 subjects in the control group).…”
Section: Resultsmentioning
confidence: 99%
“…Intervention dosage varied between 30 and 1,000 mg/day for saffron as well as 20 and 30 mg/day for crocin. Beside healthy participants (Mohamadpour et al, 2013), the selected trials also included participants with different health conditions including type 2 diabetes (Azimi et al, 2016; Ebrahimi et al, 2019; Shahbazian et al, 2019), schizophrenia (Mousavi et al, 2015), metabolic syndrome (Kermani et al, 2017), multiple sclerosis (Ghiasian et al, 2019), and participants under methadone maintenance treatment (Ghaderi et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations